Pengaruh Faktor-Faktor Fraud Diamond Dalam Mendeteksi Fraudulent Financial Reporting Dengan Moderasi Komite Audit Pada Industri Pertambangan - Fachrizka Zulfa; Hendang Tanusdjaja (Jurnal Ekonomi, 2022)
This study aims to analyze and determine the effects of financial stability, ineffective monitoring, change in auditor, and directors changes on fraudulent financial reporting, with the audit committee as moderating variable in this study. A purposive sampling technique was used to select the data in this study, and samples were obtained from 96 data on mining sector companies listed on the IDX from 2018 to 2020. This study uses two equation models, namely multiple linear regression and moderated regression analysis (MRA), to analyze secondary data in the form of company financial statements. The data processing in this study uses the Statistical Product and Service Solution version 25 software. According to the results of this study, the ineffective monitoring has a significant negative impact on fraudulent financial reporting. Meanwhile, financial stability, change in auditor, and directors changes did not have a positive or significant effect on fraudulent financial reporting. The audit committee variable can weaken the effect of financial stability, ineffective monitoring, change in auditor, and directors changes on fraudulent financial reporting.